Perception of the self and the environment - Su, Ziling (Nanyang Technological University, 2021)
The current literature examining the relationship between the need to belong and nature relatedness mainly focuses on deriving that sense of connection with nature through direct experience with nature. However, there remains limited research in exploring the influence of nature-related external factors on nature relatedness. In particular, the effect of non-nature domains such as animal loving on individual differences in nature relatedness has not been explored before. Accordingly, the present research aims to explore how animal loving, in particular pets, may influence the relationship between the need to belong and nature relatedness. The study hypothesized that a greater sense of connection to animals, in particular pets, experienced by lonely individuals would amplify their sense of connection to nature. However, based on data collected from 268 individuals, the findings did not support the hypothesis. The insignificant results of current research provide grounds for re-examination of results to have a greater understanding on individuals’ relationships with nature in relation to self-concepts.